2014
DOI: 10.1021/nn5022346
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole-Enhanced Raman Scattering

Abstract: Dark, nonradiating plasmonic modes are important in the Raman enhancement efficiency of nanostructures. However, it is challenging to engineer such hotspots with predictable enhancement efficiency through synthesis routes. Here, we demonstrate that spiky nanoshells have designable quadrupole resonances that efficiently enhance Raman scattering with unprecedented reproducibility on the single particle level. The efficiency and reproducibility of Quadrupole Enhanced Raman Scattering (QERS) is due to their hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 36 publications
1
64
0
Order By: Relevance
“…It has been recently demonstrated that the disorder in these nanoshells generates spectrally and spatially broad dark quadrupole modes that enable highly efficient and reproducible Quadrupole Enhanced Raman Scattering(QERS) on a single particle level [33]. Here we demonstrate that single particle far-field backscattering measurements of these nanoshells show interference patterns [33]. Tmatrix calculations allow us to investigate the origin of these interferences.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…It has been recently demonstrated that the disorder in these nanoshells generates spectrally and spatially broad dark quadrupole modes that enable highly efficient and reproducible Quadrupole Enhanced Raman Scattering(QERS) on a single particle level [33]. Here we demonstrate that single particle far-field backscattering measurements of these nanoshells show interference patterns [33]. Tmatrix calculations allow us to investigate the origin of these interferences.…”
Section: Introductionmentioning
confidence: 69%
“…As described in our previous publications [30][31][32][33], spiky nanoshells were produced using a surfactant-assisted seed growth method. The nanoshells used in this study have a polystyrene core with a diameter of 95 nm, with spikes estimated to be less than 68 nm in length.…”
Section: Synthesis and Dark Field Microscopymentioning
confidence: 99%
See 3 more Smart Citations